Development of smart infant-wrap (InfaWrap) device for neonates - Mohd Azrul Hisham, Mohd Adib; Mohammad Asyrul, Abd Rashid; Nur Hazreen, Mohd Hasni (Centre for Advanced Research on Energy (CARe), 2019)
Nowadays, with advanced technology, most of the parents choose to monitor their baby’s health using a pulse oximeter device. However, the existing pulse oximetry device was a hassle for infant and this makes the monitoring process difficult. In this study, we focus on the development of smart infant wrap or so-called InfaWrap device for neonates in order to accommodate clinician and parents in monitoring the heart rate and oxygen level of the baby with advanced wireless network sensor. This device easier to use, fast and accurate readings of the baby’s oxygen and heart rate.